Evaluation of the Implementation of 2013 Curriculum Vocational Batubara Regency - Albadi Sinulingga; Sanusi Hasibuan; Mauluddin M Noor (Universitas Bengkulu, 2021)
This research aims to evaluate the implementation of the 2013 Curriculum in Batubara District. The components of curriculum implementation that are evaluated include: (1) student conditions, (2) teacher conditions, (3) teacher understanding of the curriculum, (4) conditions of infrastructure, (5) lesson planning, (6) implementation of scientific-based learning, (7) ) implementation of authentic assessments, and (8) authentic assessment results related to aspects of attitudes, knowledge and skills. The evaluation model used is the Model evaluation model Stake Countenance by collecting information on curriculum implementation component data and then comparing it with the standards of the ministry of education. The population consists of 13 SMK. The research subjects were principals and teachers who were determined by purposive sampling technique. The instruments used were questionnaire sheets, observation sheets, and documentation sheets. The trial of the questionnaire instrument was conducted at a vocational school in Batubara district. Data analysis using descriptive techniques. The results of the study, the condition of the students was 93.4%, the condition of the teacher was 75%, the condition of the infrastructure was 69.3%, the understanding of the 2013 curriculum was 80%, the lesson planning or RPP was 75%, the implementation of learning was 95%, the implementation 90% authentic assessment, 82.5% authentic assessment results. Based on the results of the study, it can be concluded that all aspects in each stage have not been fulfilled maximally according to the standard.